Dietary Addition With Clostridium butyricum and Xylo-Oligosaccharides Improves Carcass Trait and Meat Quality of Huanjiang Mini-Pigs - Cai, Qiaoli; Hu, Chengjun; Tang, Wu; Jiang, Huijiao; Geng, Meimei; Huang, Xingguo; Kong, Xiangfeng (Frontiers in Nutrition, 2021)
This study was conducted to investigate the effects of dietary addition with Clostridium butyricum (CB) and xylo-oligosaccharides (XOS) on growth performance, carcass trait, and meat quality of pigs. A total of 128 Huanjiang mini-pigs with an initial body weight of 9.5 ± 0.1 kg were randomly assigned to one of four groups. The pigs in control (Con) group were fed a basal diet and those in the experimental groups were fed the basal diet supplemented with 0.05% CB (CB group), 0.02% XOS (XOS group), or 0.05% CB + 0.02% XOS (CB + XOS group). Eight replicate pens were used per group with four pigs per pen. On days 28, 56, and 84 of the trial, the growth performance, carcass trait, and meat quality were evaluated. The results showed that dietary CB addition decreased (p < 0.05) the average daily gain and increased (p < 0.05) the ratio of feed intake to body weight gain at day 28 of the trial; CB, XOS, and CB + XOS addition increased (p < 0.05) the backfat thickness at day 84 of the trial compared with the Con group. Dietary CB, XOS, and CB + XOS addition increased (p < 0.05) the pH45min, while decreased (p < 0.05) the marbling score at day 28 of the trial compared with the Con group. Dietary CB + XOS addition increased (p < 0.05) the contents of Ala, Arg, Asp, Gly, His, Leu, Lys, Met, Phe, Ser, Thr, Tyr, and Val in muscle at day 56 of the trial. At day 84 of the trial, dietary CB addition increased the contents of nonessential amino acid (NEAA), total amino acid (TAA), and monounsaturated fatty acid (MUFA), while decreased (p < 0.05) the percentage of C20:1 in muscle compared with the Con group. Collectively, dietary addition with 0.05% CB and 0.02% XOS could not alter the growth performance, but increase carcass trait, meat quality, and muscular nutrient contents in Huanjiang mini-pigs.